1973
DOI: 10.1111/j.1471-4159.1973.tb04248.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Maternal Hyperphenylalaninemta: Disaggregation of Fetal Brain Ribosomes

Abstract: Disaggregation of polyribosomal structures has been demonstrated in fetal rat brains following treatment of the maternal animal with para‐chloro‐d,l‐phenylalanine (used primarily to inhibit maternal phenylalanine hydroxylase, EC 1.14.3.1) and with phenylalanine (used to raise the level of circulating phenylalanine in maternal and fetal plasma). Since highly disaggregated polyribosomal systems cannot support normal levels of protein synthesis in vitro, it has been postulated that the composition of the free ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1974
1974
1987
1987

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…However, as the 5-day-old and older neonates are not hypoglycemic, other mechanisms must be involved. Although food restric tion of control mothers produced no real detrimental effect per se, it may play a role in the Tx mother who has many metabolic abnormalities and does not supply the fetus with normal amounts of substrate [16,17,20], Deficiencies of single amino acids in the mother such as asparagine [29] and taurine [14] during nursing, or maternal protein deficiency pre-and postnatally [11], result in impairment of brain devel opment in the offspring just as does hyperphenylalaninemia [5] which is a well documented disorder which leads to mental retardation.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the 5-day-old and older neonates are not hypoglycemic, other mechanisms must be involved. Although food restric tion of control mothers produced no real detrimental effect per se, it may play a role in the Tx mother who has many metabolic abnormalities and does not supply the fetus with normal amounts of substrate [16,17,20], Deficiencies of single amino acids in the mother such as asparagine [29] and taurine [14] during nursing, or maternal protein deficiency pre-and postnatally [11], result in impairment of brain devel opment in the offspring just as does hyperphenylalaninemia [5] which is a well documented disorder which leads to mental retardation.…”
Section: Discussionmentioning
confidence: 99%
“…Loo et al [24] described a disruption in the normal brain ganglioside pattern and reduced sialoglycoproteins. Copenhaver et al [25] found that the polyribosomal structure in rat fetal brains was disaggregated, and Okano et al [26] supported this in observing reduced polysomes with increased numbers of disomes and monosomes in fetal brains. Taken Future Directions in Maternal PKU Maternal PKU represents an unusual ex ample of biochemical disequilibrium trans mitted across the placenta and producing fetal damage.…”
Section: Pathogenesis Of the Fetal Damagementioning
confidence: 61%
“…Animal experiments studying maternal PKU in terms of brain damage have shown the behavioural abnormalities in the offspring (Kerr et al, 1968), amino acid imbalances (Carver et al, 1965), disaggregation of polysomes (Wong et al, 1972, Copenhaver et al, 1973, changes in the amounts of DNA, RNA and protein (Brass et al, 1982;Spero and Yu, 1983), low pyruvate kinase (Wapnir et al, 1977) and decreased transmitter levels (Brass et al, 1982). However, to our knowledge studies concerning congenital heart disease using animal models of maternal PKU have not been reported.…”
Section: Discussionmentioning
confidence: 91%
“…(The incidence inthe general population is 0.8%). Mental retardation due to maternal PKU may be associated with disturbances in MS received 26.4.85 Accepted 1.8.85 protein synthesis in the fetal brain during development (Wong et al, 1972;Copenhaver et al, 1973). However, there are few reports on the cause of congenital heart disease in maternal PKU.…”
mentioning
confidence: 96%